Factors Associated with the Chance of Carrying out a Primary Cesarean in a University Hospital - Maria Celeste Osório Wender; Rafaela Girardi Duarte; Gabriel Cardozo Muller; Rosaura Rolim Cavalheiro; Yanick Adolfo Leal Correia Silva; Cristiane Carboni; Edimárlei Gonsales Valério (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective The present study seeks to identify the associated factors that increased primary cesarean delivery rates. Methods This was a cross-sectional study that evaluated the number of primary cesarean sections performed in the years 2006 and 2018 at the Hospital de Clínicas de Porto Alegre (HCPA, in the Portuguese acronym), through the collection of data from the medical records of the patients. Results Advanced maternal age, twin pregnancy, and higher body mass index (BMI) became more frequent in 2018 in comparison with 2006. To mitigate the impact of confounding in comparisons among groups, we made an adjustment by propensity scores and detected significant differences when comparing both age groups on twin pregnancy rates, gestational diabetes mellitus, and thyroid disease. Conclusion Data from the present study can be used to prevent and improve the management of morbidities, impacting on better outcomes in obstetrical practice.